The relationship between the functional status of regulatory mechanisms and the effectiveness of technical and tactical operations in boxers - Shchedrina Yu.A.; Melnikov D.S.; Seliverstova V.V.; Aimbetova N.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study – is to analyze the interrelationships between psychophysiological parameters and characteristics of heart rate variability, which affect the effectiveness of technical and tactical actions of boxers during competitions. Methods and structure of the study. The study involved boxers aged 18 to 20 years, among whom there were 15 men and 10 women. To assess the functional state, the Varikard 2.52 hardware and software package was used, which was used to record statistical and spectral indicators of heart rate variability. The assessment of the functional state of the central nervous system was carried out using the UPFT-1/30 "Psychophysiologist" psychophysiological testing device. Results and conclusions. The results of the study showed that the percentage of effective punches in female boxers is inversely proportional to the stability of the reaction in a simple visual-motor reaction, tremometry indicators and the stress index of heart rate variability. In male boxers, the effectiveness of punches is associated with indicators of simple visual-motor reaction, reaction stability, and VLF-wave values reflecting the level of stress on the athlete’s body.